1982
DOI: 10.1093/infdis/146.6.746
|View full text |Cite
|
Sign up to set email alerts
|

Possible Alteration of Normal Mechanisms of Endotoxin Toxicity in Vivo by Actinomycin D

Abstract: The effect of actinomycin D on the sensitivity of endotoxin-responsive (C3HeB/FeJ) and endotoxin-unresponsive (C3H/HeJ) mice to challenge with purified lipopolysaccharide (LPS) of Escherichia coli strain O55:B5 was examined using an experimental protocol of adoptive transfer of lymphoid cells into lethally irradiated recipients. Earlier results--that in the absence of actinomycin D, the ability of LPS to cause a lethal response in the immunologically chimeric mice reflected the phenotypic response of the donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Bradley and Bond (8) found that combinations of pactamycin and endotoxin administered simultaneously killed mice more rapidly than either drug alone; in vitro, the two drugs used in combination increased the in vitro fragility of renal lysosomes. Brown and Morrison (10) reported that simultaneous administration of actinomycin D to endotoxinresponsive mice increased by several orders of magnitude the susceptibility of these mice to the lethal effects of endotoxin. In contrast, Rifkind and Palmer (23) noted that three cationic cyclic polypeptide antibiotics, polymixin B sulfate, colistin sulfate, and tyrocidine hydrochloride, neutralized endotoxin lethality in chicken embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Bradley and Bond (8) found that combinations of pactamycin and endotoxin administered simultaneously killed mice more rapidly than either drug alone; in vitro, the two drugs used in combination increased the in vitro fragility of renal lysosomes. Brown and Morrison (10) reported that simultaneous administration of actinomycin D to endotoxinresponsive mice increased by several orders of magnitude the susceptibility of these mice to the lethal effects of endotoxin. In contrast, Rifkind and Palmer (23) noted that three cationic cyclic polypeptide antibiotics, polymixin B sulfate, colistin sulfate, and tyrocidine hydrochloride, neutralized endotoxin lethality in chicken embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Serum (225 l) was incubated at 37°C for 10 min with shaking in 96-well plates with 75 l of 2% sulfanilamine and 0.2% N-1-naphthylenediamine dihydrochloride in 1.2 N HCl. Then the nitrite concentration was determined from the optical density at 540 nm using a microplate reader and reference to a standard curve constructed with known concentrations of NaNO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Several substances have been documented to enhance by more than 1000-fold the sensitivity of mice to the lethal and hepatotoxic effects of LPS, including galactosamine [1], actinomycin D [2], and ␣-amanitin [3]. Although the mechanisms of sensitization by these metabolic inhibitors have not been elucidated in detail, blocking of protein synthesis by inhibition of RNA synthesis may be involved.…”
Section: Lipopolysaccharide (Lps)mentioning
confidence: 99%
“…Protein synthesis inhibition has been shown to increase LPS-induced endothelial cell detachment (Harlan et al, 1983a) and cytotoxicity (Harlan et al, 1983a;Pohlman and Harlan, 1989) in vitro. In animal models, administration of sublethal doses of protein synthesis inhibitors sensitize animals to LPS-induced mortality (Brown and Morrison, 1982;Seyberth et al, 1972;Wallach et al, 1988), whereas pretreatment with subthreshold levels of LPS desensitize animals to subsequent LPS challenge (Greisman and Hornick, 1976). These studies suggest that LPS can stimulate protein synthesis-dependent mechanismb) that can protect the endothelium against a subsequent LPS exposure.…”
Section: Mediummentioning
confidence: 99%